Super-elderly treatment resistant depression patient treated with modified electroconvulsive therapy： a case report - Chong Shan; Xiong Na'na; Fan Tengteng (Sichuan jingshen weisheng, 2025)
The paper reported a case of super-elderly patient with treatment-resistant depression who underwent modified electroconvulsive therapy （MECT）. The patient was an 87-year-old female presented to the hospital with an 8-year history of depressive disorder marked by intermittent episodes， who exhibited poor response to various antidepressants while achieved a significant improvement after receiving MECT. In the past two years， the patient experienced a recurrence of depression following life stress events. The condition showed improvement with the administration of MECT. However， after discontinuation of MECT， the depression relapsed multiple times， prompting rehospitalization for continued MECT to sustain clinical benefits. The patient demonstrated overall tolerable adherence to MECT. Based on research of domestic and international， this paper explored treatment options for super-elderly patients with treatment-resistant depression， aiming to provide insights into the application of MECT in the management of depression among super-elderly patients with depression. ［Funded by National Key Research and Development Project （number， 2019YFC0118502）］